(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Retirement should be understood not as a period of decline in activity, but as a significant life transition that can open the door to healthier, more active living. In the context of healthy ageing, this stage of life offers an important opportunity for positive behaviour change. Yet, despite this potential, there remains limited attention to interventions specifically designed to encourage physical activity and reduce sedentary behaviour as individuals move towards and into retirement. Promoting physical activity during this transition requires more than simply encouraging people to exercise. It demands an appreciation of retirement as a broader life process, shaped by changing routines, shifting identities, emotional adjustment, and social circumstances. Meaningful intervention in this space must therefore consider the factors that influence behaviour change in a holistic way. Motivation, knowledge, confidence, self-efficacy, emotional readiness, and social support all emerge as central elements. Equally important is the extent to which workplaces and wider systems help prepare individuals for retirement in a way that supports health and wellbeing. What becomes clear is that successful approaches need to be tailored, bio-psycho-social, and responsive to the lived realities of people approaching retirement. They should not focus solely on physical activity as an isolated behaviour, but embed it within the wider retirement journey. Follow-up, social connectedness, and personalised support appear essential if lifestyle change is to be sustained over time. From this understanding, a conceptual framework can be recognised in which physical activity promotion is the most effective when it integrates behavioural change principles with practical, socially grounded strategies. Such a perspective offers valuable direction for future intervention design and contributes meaningfully to broader policy conversations on active and healthy ageing. Ultimately, supporting people through the retirement transition in this way positions physical activity not merely as a health recommendation, but as part of a positive and supported pathway into later life. Keywords: Retirement transition; physical activity promotion; behaviour change; healthy ageing; bio-psycho-social support